(3GdYGOGJ GdSHY ddeQGgbjf GdCcKQ aYGdjIs (3GdOdjd GdCcjO ddfLGM aj aJQI GdeQGgbIs - (3chaj, Tjfs ((3GdQjGVs (3ecJHI LQjQs, 2005)
(3chfc eQGgbkG CeQ QGFY heKjQ ddJMOj(B. (3aj cJGHg (B"(3GdYGOGJ GdSHY ddeQGgbjf GdCcKQ aYGdjI(B"(3, jWqHb GdeDda Tjf chaj GdeHGOF GdCSGSjI ddYGOGJ GdSHY GdTgjQI Ydi GdeQGgbjf hGdbVGjG GdYSjQI hbQGQGJ GdMjGI GdeJZjQI GdJj jhGLghfgG(B. (3jbOe Tjf chaj OdjdkG NWhI HNWhI, HCSdhH eeJY, deSGYOI GdeQGgbjf aj JMSjf UhQJge CeGe CfaSge, haj HfGA YdGFb UOGbI bhjI, hJMbjb CgOGage, hZjQ Pdc cKjQ, aEf gPG GdcJGH jRNQ HGdUhQ hGdCacGQ, hGdGbJHGSGJ, hbUU eKjQI dG oJUOb Yf eQGgbjf Mbjbjjf ef LejY CfMGA GdYGde(B. (3Ef gPG GdcJGH SjLPH GdeQGgbjf ceG de jaYd Cj cJGH BNQs
(3eJhGaQ efg EYGOI GdWHYI GdChdi dYGe (B2023 (3aj ecJHI GdRGhjI GdMeQGAs
(3eJhGaQ efg GdWHYI GdGhdi dYGe (B2020 (3HecJHI GdRGhjI GdMeQGAs
(3eJhGaQ efg GdWHYI GdKGefI dYGe (B2011 (3aj ecJHI GdRGhjI GdMeQGAs
(3eJhGaQ efg GdWHYI GdYGTQI dYGe (B2013 (3aj ecJHI eUQ GdQFjSjIs
(3GdfU eJQLe Edi GddZI GdYQHjI ef GddZI GdEfLdjRjIs
1 2 12 13
Keywords: Success -- Psychological aspects; Teenagers -- Conduct of life; (3COH YQHjs; (3GdTHGHs; (3GdeQGgbIs; (3GdeQGgbhfs; (3GdfLGM GdTNUjs; (3JYdjes; (3bUU OjfjIs; (3cJH ddCWaGds